The development of professional skills through blogs and personal websites - VEVERITA, Tatiana (Acta et Commentationes, Sciences of Education, 2024)
The article proposes and evaluates how a teacher’s blog and personal website can become useful learning tools for acquiring professional skills. Learners are required, after opening a blog/personal website, to document the activities carried out in the classroom, reflect on these activities during the training period, and use tags as elements of self-reflection on the skills developed during the training. To monitor the learners’ progress in developing the teacher’s blog/personal website, a questionnaire is used at the beginning and the end of the training period. This information is supplemented with an analysis of the content published on the blogs/websites. The study will also reveal whether the participating teachers consider the blogs/websites valid tools for acquiring professional skills, whether they are satisfied with the teaching-learning process, and whether they would recommend these tools to other educators.